E-LEARNING TECHNOLOGIES IN PROMOTING YOUTH SAFETY - Vārpiņš, Kaspars; Samuseviča, Alīda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
In today's changing environment, with different risks and threats, there is a need to find new ways to educate young people about existing security threats, both physical and virtual. To facilitate this, it is necessary to regularly improve the knowledge of various members of the society on various safety issues. By timely educating members of the society about the various possible unsafe situations and risks, its members will be prepared for an unsafe situation and will know what to do, thus avoiding unnecessary chaos and panic. In addition, it should be understood that today's new opportunities for e-learning and its processes, are reasons to revise the pedagogical process as such, as e-learning platforms can achieve a more personal effect rather than make the learner feel like one small and unimportant part in the audience. Although there may be a loss of personal contact between the teacher and the learner, but the interaction in the large audience is minimal as well. For this purpose, analysis and evaluation of documents, scientific, pedagogical and psychological literature was carried out, as well conclusions were summarized on the possible impact of e-learning technologies on the promotion of youth safety.